PENGARUH DEFISIT ANGGARAN DAN PDB TERHADAP UTANG LUAR NEGERI INDONESIA - Yulia Lestari Ningsih; Diana Sapha A.H. (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study aims analyze the effect of the budget deficit, GDP and foreign debt of Indonesia from 2000 to 2018 using OLS model with multiple linier regression method . The results of this study indicate that simultaneous budget deficit and GDP have a positive and significant effect on foreign debt of Indonesia.Keywords : Foreign debt, Budget Deficit, GDP